2019
DOI: 10.4108/eai.13-9-2018.156150
|View full text |Cite
|
Sign up to set email alerts
|

Analysing cross-cultural design in advergames: a comparison between the UK and Brazil

Abstract: This paper presents the findings from a study of advergame design elements paying particular attention to cross-cultural consumer attitudes towards advergames and sponsored brands. From a thorough literature review, an integrated framework for advergames across cultures (CAKE) has been designed, composed of game design elements, brand perspectives and cultural characteristics. Utilising the CAKE framework, 40 mobile advergames from Brazil and the UK were studied through a content analysis, followed by an inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 32 publications
0
12
0
Order By: Relevance
“…In this research, the national culture will be used as a key variable in the differentiation of consumer behavior in the electronic channel from two nations with distinct cultures, according to the indexes of the dimensions that make up the national culture. According to Wanick et al (2019), cross cultural study in consumer behavior has had a great attention to comparisons between eastern and western countries, however, Latin America has been lagged from these studies. This study focuses on Colombia and Spain and aims to help fill an important gap in the scientific literature on Latin American culture (See-Pui, 2013;Verdugo and Ponce, 2020) by studying Colombian consumers and comparing them with Spanish consumers.…”
Section: National Culturementioning
confidence: 99%
“…In this research, the national culture will be used as a key variable in the differentiation of consumer behavior in the electronic channel from two nations with distinct cultures, according to the indexes of the dimensions that make up the national culture. According to Wanick et al (2019), cross cultural study in consumer behavior has had a great attention to comparisons between eastern and western countries, however, Latin America has been lagged from these studies. This study focuses on Colombia and Spain and aims to help fill an important gap in the scientific literature on Latin American culture (See-Pui, 2013;Verdugo and Ponce, 2020) by studying Colombian consumers and comparing them with Spanish consumers.…”
Section: National Culturementioning
confidence: 99%
“…It will directly help the business readers of this study to make business decisions in their companies. Besides, these detailed analyzes will provide theory on consumer behavior in a period of a pandemic since these intercultural studies on consumer behavior and help fill an essential gap in the scientific literature on Latin American culture ( See-Pui, 2013 ; Verdugo and Ponce, 2020 ; Wanick et al., 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…In this research, the national culture is a critical variable in differentiating consumer behavior in Covid-19 times from three nations with Latin American cultures (Mexico, Colombia, and Ecuador) that have lagged behind these intercultural studies in behavior. Of the consumer and help fill an essential gap in the scientific literature on Latin American culture ( See-Pui, 2013 ; Verdugo and Ponce, 2020 ; Wanick et al., 2019 ). Table 2 shows the indices of the six cultural dimensions for the selected markets, according to Hofstede, 2020a , Hofstede, 2020b .…”
Section: Conceptualization Of Purchase Behavior In Times Of Pandemicmentioning
confidence: 99%
“…All the above concepts proposed by the social cognitive theory can be applied in creating the virtual reality components of the advergames used in awareness campaigns. The second source draws largely on the approach suggested by Wanick et al (2019) for designing advergames. Wanick et al (2019) present a holistic framework that consists of four layers.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…One of the important findings is that the game designers and developers have to know how to persuade players and gain their engagements by paying attention to the key game features and the flow of the mobile advergame. Wanick et al 2019 in their research studied advergame elements of design used and concluded that there is a cultural difference in the attitude towards advergames.…”
Section: Introductionmentioning
confidence: 99%